2023
DOI: 10.1111/cid.13203
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bisphosphonate treatment on bone substitute performance in osteoporotic conditions

Abstract: Objective: Considering the elevated number of osteoporotic patients in need of bone graft procedures, we here evaluated the effect of alendronate (ALN) treatment on the regeneration of bone defects in osteoporotic rats. Bone formation was histologically and histomorphometrically assessed in rat femoral condyle bone defects filled with bone graft (Bio-Oss ® ) or left empty.Methods: Male Wistar rats were induced osteoporotic through orchidectomy (ORX) and SHAM-operated. The animals were divided into three groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 82 publications
(165 reference statements)
0
2
0
Order By: Relevance
“…During the process of cement injection into the defect area, it was observed that the anti-washout property maintained the shape of the cement from being flushed away by blood. ALN is one of the most commonly used anti-osteoporosis drugs, which can effectively inhibit bone resorption of osteoclasts and reduce osteolysis, has been widely used in clinical practice in recent years [ [40] , [41] , [42] ]. Studies have reported that implemented local ALN delivery to promote bone repair by loading ALN on injectable hydrogels could effectively promote bone regeneration in osteoporotic rats in vivo [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the process of cement injection into the defect area, it was observed that the anti-washout property maintained the shape of the cement from being flushed away by blood. ALN is one of the most commonly used anti-osteoporosis drugs, which can effectively inhibit bone resorption of osteoclasts and reduce osteolysis, has been widely used in clinical practice in recent years [ [40] , [41] , [42] ]. Studies have reported that implemented local ALN delivery to promote bone repair by loading ALN on injectable hydrogels could effectively promote bone regeneration in osteoporotic rats in vivo [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…ALN is one of the most commonly used anti-osteoporosis drugs, which can effectively inhibit bone resorption of osteoclasts and reduce osteolysis, has been widely used in clinical practice in recent years [ [40] , [41] , [42] ]. Studies have reported that implemented local ALN delivery to promote bone repair by loading ALN on injectable hydrogels could effectively promote bone regeneration in osteoporotic rats in vivo [ 42 , 43 ]. It is also confirmed that loading ALN in a dual-delivery system with substance P could effectively regulate osteogenesis-osteoclastogenesis balance for promoting immediate implant osseointegration [ 44 ].…”
Section: Resultsmentioning
confidence: 99%